Dickkopf-3 Upregulates VEGF in Cultured Human Endothelial Cells by Activating Activin Receptor-Like Kinase 1 (ALK1) Pathway - Busceti, Carla L.; Marchitti, Simona; Bianchi, Franca; Di Pietro, Paola; Riozzi, Barbara; Stanzione, Rosita; Cannella, Milena; Battaglia, Giuseppe; Bruno, Valeria; Volpe, Massimo; Fornai, Francesco; Nicoletti, Ferdinando; et al. (Frontiers in Pharmacology, 2017)
Dkk-3 is a member of the dickkopf protein family of secreted inhibitors of the Wnt pathway, which has been shown to enhance angiogenesis. The mechanism underlying this effect is currently unknown. Here, we used cultured HUVECs to study the involvement of the TGF-beta and VEGF on the angiogenic effect of Dkk-3. Addition of hrDkk-3 peptide (1 or 10 ng/ml) to HUVECs for 6 or 12 hrs enhanced the intracellular and extracellular VEGF protein levels, as assessed by RTPCR, immunoblotting, immunocytochemistry and ELISA. The increase in the extracellular VEGF levels was associated to the VEGFR2 activation. Pharmacological blockade of VEGFR2 abrogated Dkk-3-induced endothelial cell tubes formation, indicating that VEGF is a molecular player of the angiogenic effects of Dkk-3. Moreover, Dkk-3 enhanced Smad1/5/8 phosphorylation and recruited Smad4 to the VEGF gene promoter, suggesting that Dkk¬-3 activated ALK1 receptor leading to a transcriptional activation of VEGF. This mechanism was instrumental to the increased VEGF expression and endothelial cell tubes formation mediated by Dkk-3, because both effects were abolished by siRNA-mediated ALK1 knockdown. In summary, we have found that Dkk-3 activates ALK1 to stimulate VEGF production and induce angiogenesis in HUVECs.